LANGUAGE AND GENDER IN ENGLISH LANGUAGE TEACHING - Murni Mahmud (TEFLIN, 2010)
Abstract: This paper highlights the impact of gender differences in English Language Teaching. It explores studentsâ learning styles as affected by the notions about men and women differences in communication. The data collected in 2008 from 20 males and 20 femalesâ English students of the State University of Makassar. It is to reveal their attitudes towards speaking to different sex, strategy to express opinion, group work preferences, activeness/passiveness, and their perception to increase English skills dealing with sex difference. It is revealed that female than male students were reluctant to speak to different sex; females preferred the direct way to express opinions (writing), work with the same sex, and tended to be passive in class. In addition, females saw the high possibility to increase their English skills by working with the same sex but the reverse is true for males. These different styles of female and male students in learning English were affected by the notions of womenâs language.